ANALISIS KINERJA PERAWAT DALAM PENGENDALIAN INFEKSI NOSOKOMIAL DI RSU PKU MUHAMMADIYAH BANTUL YOGYAKARTA - Herpan, .; Wardani, Yuniar (Universitas Ahmad Dahlan, 2012)
Background: Nosocomial infection is an important health care problem worldwide. Nosocomial infections in the hospital at about 9% (variation 3- 21%) or over 1.4 million patients admitted to hospi-tals around the world. Nosocomial infections pose some problems, namely an increase in morbid-ity and mortality, the addition of day care, the increasing cost of care and dissatisfaction with both pa-tients and their families. Nosocomial infection control efforts are very complex and involves a variety of targets including hospital personnel, patients, medical equipment, treatment rooms, and the envi-ronment. The purpose of this study was to mengetahuai performance of nosocomial infection con-trol nurse in PKU Muhammadiyah Hospital in Bantul, Yogyakarta. Methods: This study was a type of observational analytic study using quantitative cross- sectional survey design. The sample size was of the study was 50 nurses. The sampling technique used Sampling Random sampling techniques with systematic sampling. Data was taken using a ques-tionnaire. Results: Based on the results of the bivariate test there were three variables that were statistically significant, namely knowledge (p value = 0.000 and RP = 7.115), attitude (p value = 0.000 and RP = 6.519) and skills (p value = 0.000 and RP = 6.519). Non- significant variables: education (p value = 0.486 and RP = 0.542) and training (p value = 0.670 and RP = 1.432). Conclusion: There was a statistically significant relationship between knowledge, attitudes and skills in nosocomial infection control and there was no statistically significant relationship between education and training in nosocomial infection control. Key words: nosocomial infection control, nurse performance, cross sectional.